Association of T cell dysfunction with the presence of IgG autoantibodies on CD4+ lymphocytes in haemophilia patients: results of a 10-year study - Daniel, Volker; Süsal, Caner; Weimer, Rolf; Zipperle, Silvia; Kröpelin, M.; Zimmermann, R.; Huth-Kühne, Angela; Opelz, Gerhard (Clinical & experimental immunology, 1996)
HIV induces progressive dysfunction followed by numerical depletion of CD4+ lymphocytes. IgG autoantibodies and gp120-containing immune complexes have been implicated in the pathogenesis of AIDS. We carried out a longitudinal study in 19 HIV- and 72 HIV+ haemophilia patients over a 10-year period in order to investigate a possible relationship between the occurrence of autoantibodies and CD4+ lymphocyte changes. IgM, IgG, C3d and gp120 on the surface of CD4+ lymphocytes were determined in heparinized whole blood with flow cytometry and double-fluorescence. The in vitro response of autoantibody-coated cells was tested in cell cultures with concanavalin A (Con A), phytohaemagglutinin (PHA), pokeweed mitogen (PWM), anti-CD3 MoAb or pooled allogeneic stimulator cells (MLC). After a 10-year follow up, 12 of 71 HIV+ and 16 of 19 HIV- haemophilia patients showed no evidence of immunoglobulins on circulating CD4+ lymphocytes. HIV- haemophilia patients without autoantibodies had CD4+and CD8+ cell counts in the normal range (957 ± 642/μl and 636 ± 405/μl) and normal T cell responses in vitro (mean relative response (RR) ≥ 0.7). In contrast, HIV+ haemophilia patients showed immunological abnormalities which were associated with the autoantibody and immune complex load of CD4+ blood lymphocytes. HIV+ patients without autoantibodies had a mean CD4+ lymphocyte count of 372 ± 274/μl, a mean CD8+ lymphocyte count of 737 ± 435/μl, and normal T lymphocyte stimulation in vitro (mean RR ≥ 0.7). HIV+ patients with complement-fixing IgM on CD4+ lymphocytes had somewhat lower CD4+ (255 ± 246/μl, P = NS) and CD8+ (706 ± 468/μl, P = NS) lymphocyte numbers, and also normal T lymphocyte stimulation (mean RR ≥ 0.7) in vitro. However, patients with complement-fixing IgG autoantibodies showed a strong decrease of CD4+ (150 ± 146/μl, P < 0.02) and CD8+ (360 ± 300/μl, P < 0.02) lymphocytes and impaired CD4+ lymphocyte stimulation in vitro with a mean RR of 0.5 ± 0.5 for Con A (P = NS), 0.7 ± 0.8 for PHA (P < 0.03), 0.4 ± 0.4 for PWM (P = NS), 0.8 ± 1.2 for anti-CD3 MoAb (P < 0.04) and 0.7 ± 1.0 for pooled allogeneic stimulator cells (P = 0.05). Patients with gp120-containing immune complexes on CD4+ blood lymphocytes demonstrated strongly decreased CD4+ (25 ± 35/μl, P < 0.0001) and CD8+ (213 ± 212/μl, P < 0.006) lymphocyte counts as well as strongly impaired T lymphocyte responses in vitro upon stimulation with PHA (RR 0.2 ± 0.1, P < 0.02), PWM (RR 0.2 ± 0.2, P = 0.05), anti-CD3 MoAb (RR 0.1 ± 0.1, P < 0.04), and allogeneic stimulator cells (RR 0.2 ± 0.1, P < 0.02). These data led us to speculate that autoantibody formation against CD4+ lymphocytes is an important mechanism in the pathogenesis of AIDS. We hypothesize that autoantibodies against circulating CD4+ lymphocytes inhibit CD4+ cell function, especially the release of cytokines, and induce CD4+ cell depletion. The reduction and dysfunction of CD4+ lymphocytes may be responsible for the CD8+ cell depletion observed in HIV+ patients.
Elektronische Reproduktion der Druck-Ausgabe 29. Oktober 2003
Gesehen am 19.08.2024